A transient peak of infections during onset of rheumatoid arthritis: a 10-year prospective cohort study. Issue 8 (1st September 2014) - Arleevskaya, Marina I; Gabdoulkhakova, Aida G; Filina, Yulia V; Miftakhova, Regina R; Bredberg, Anders; Tsybulkin, Anatoly P
Abstract : Objectives: The role of infection in rheumatoid arthritis (RA) has not been determined. We aimed to document the infectious burden and some aspects of antibacterial immunity in a large and prospective cohort study of RA patients in the early and late stages of the disease and in their relatives predisposed to RA. Setting: Clinical and laboratory examination of all individuals enrolled in the study was performed in the Republican Clinical Hospital, Kazan, Russia. Participants: 376 patients with RA, 251 healthy first-degree relatives and 227 healthy controls without a family history of autoimmune disease (all females) were examined twice annually over more than 10 years. Primary and secondary outcome measures: The following parameters were investigated: type, duration and frequency of infections, bacterial colonisation and serum levels of IgG to bacteria, serum levels of total Ig, plasma cytokine levels, granulocyte reactive oxygen species production, lysozyme activity and phagocytosis. Results: There were no significant differences in infection rate between healthy controls (median 14 days/year) and RA patients (13). However, infection rates were higher (p<0.001) in healthy relatives (53) and early stage patients (62), which groups also showed heavy bacterial skin colonisation. In contrast, late stage patients had fewer infection days (12; p<0.001) than healthy controls, although bacterial colonisation was still heavy. Phagocyte function and antibacterial antibody generation, together with compensatory cytokine production, were observed to be subnormal in the healthy relatives as well as in RA patients. Conclusions: We observed a marked increase in overall infections at the time of RA onset, and signs of a defective antibacterial defence mechanism, contrasting with fewer infections in the late RA stage. It can be speculated that frequent early infections initiate a compensatory immune hyper-reactivity which reduces the infection load while stimulating the development of RA in predisposed individuals.